Brand and Reputation as Quality Signals on Regulated Markets - Markus Kick; Martina Littich (Springer Gabler, 2015)
Legislation put into effect in 2009 has dramatically altered the health insurance system in Germany by introducing premium equality in order to foster new competition between the German statutory health insurance funds based on quality rather than price. The statutory health insurance (SHI) funds have reacted quickly by offering new benefits and services. However, we assume that consumers are influenced not only by product attributes but also by signals of quality, such as those delivered by corporate reputation, which can act as an information surrogate. The results of our choice-based conjoint experiment show that benefits such as elective tariffs, bonus programs, complementary insurance offers, voluntary coverage, and extended services significantly influence consumer choice of statutory health insurance. These findings argue for the success of the public policy strategy of the German government. Our findings indicate that reputation is fairly important in product choice when compared with product-based attributes. As a consequence of these findings, funds should not only adapt their offerings with regard to the benefits that insurants value the most but also place emphasis on corporate reputation management.
Additional information: Reworking the story to a bigger and more pragmatic target audience. Cf. Kick M. (2015): Selected Essays on Corporate Reputation and Social Media. Springer Gabler, Wiesbaden, https://doi.org/10.1007/978-3-658-08837-8
Keywords: 330; Regulation; Statutory Health Insurance; Corporate Reputation; Branding